PROFESSIONAL MASTERY OF A TEACHER AT A PROFESSIONAL PRE-HIGHER EDUCATION INSTITUTION IN THE FIELD OF RAILWAY TRANSPORT - Береза, Р.; Єпов, А.; Томіліна, О. (Нові горизонти педагогічної майстерності: від традицій до інновацій, 2025)
The article explores the essence of the professional mastery of a teacher at a professional pre-higher education institution that trains specialists for the railway transport sector. Emphasis is placed on the key components of pedagogical excellence, the specifics of teaching in a changing transport industry, digitalization, and the implementation of dual education. The practice-oriented approach to training is highlighted, and the importance of industrial internships, excursions, and meetings with industry representatives is justified. Modern approaches to the formation of professional mastery are highlighted, and the personal and professional qualities necessary for an effective educational process are described. Regulatory support for practice is disclosed, and empirical data on its effectiveness is provided.